Analysis of Working Capital, Labor, Technology, and Land Ownership on Rice Farmers' Income - Anang Safi'i; Supawi Pawenang; Anita Wijayanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to examine the influence of working capital, labor, technology, and land ownership on the income of rice farmers in the Setyo Bhakti Watualang Farmers Group, Ngawi. This research uses a quantitative research design. The population of this study consists of 103 rice farmers in the Setyo Bhakti Watualang Farmers Group, Ngawi. The sampling technique used in this study is a census with a total sample of 103 respondents. Data collection is carried out using questionnaires. The data analysis techniques used include statistical analysis, namely multiple linear regression test, F test, t test, and the coefficient of determination. Research results indicate that working capital, labor, technology, and land ownership simultaneously and significantly affect the income of rice farmers in the Setyo Bhakti Watualang Farmer Group, Ngawi. Recommendations from this study suggest that the government can prioritize providing working capital at low-interest rates to farmers. In addition, members of the Setyo Bhakti Farmer Cooperative in Watualang village can utilize technology to increase agricultural production, and to obtain additional capital, it is recommended for farmer group members to actively participate in programs organized by the government, related agencies, and the Farmer Group management so that their income can increase and improve compared to before.